DIVERSITY OF REGENERATING TREE SPECIES IN RESPONSE TO DIFFERENT SOIL CHEMICAL PROPERTIES IN PARKLAND AREA OF GWARZO LOCAL GOVERNMENT, KANO STATE - ABDUL RASHID INUWA; H.BILYAMINU (The Bioscan, 2020)
This research covered the parkland of Gwarzo, along Kano road and was aimed at determining the composition and density of regenerating tree species and the diversity in terms of richness and evenness. The chemical properties of the soil were also determined. The findings of the research showed that, within the 50 systematically sampled plots of 25x25m, a total of 920 regenerating stems were encountered belonging to 16 different species, distributed within 11 families. Family Fabacaceae had the highest number of four (4) species, followed by Anacardiaceae and Combretaceae with two (2) species each. Families Bombacaceae, Moraceae, Maliaceae, Ebanaceae, Vertenaceae, Rhamnaceae, Myrtaceae and Zygophyllaceae had one (1) species each. Poor regeneration was reported as the number of seedlings was very low compared to the saplings and trees. Diospyros mespiliformis, Eucalyptus camaldulensis, Azadirachta indica, and Parkia biglobosa showed a high regeneration potential. Fewer seedling and and saplings were recorded for Terminalia macroptera, Ficus sycomorus and Anogeissus leiocarpus. The Shannon wiener diversity index value (H’) is moderate for all the classes; Seedlings (2.0572), Saplings (2.4394) and Trees (2.6502). Soil organic matter, available phosphorous, total Nitrogen, K, Mg, and Na decrease with increasing depth.